A note on models for phases with order/disorder transitions in thermodynamic software and databases - Sundman, Bo (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The Calphad method is an important tool to assist the development of new alloys.There are several different thermodynamic software and databases available for such calculations.In some of these alloys there are is an important order/disorder transition,like in superalloys (Ni-based) or Al-Ti alloys. This paper describes the modeling of suchsystems and a new software that has improved the implementation of the modeling of thistransition which can extend the composition range of the application of the model.